Anxiety and depressive disorders in medical students - V. A. Strizhev; E. O. Boyko; L. E. Lozhnikova; O. G. Zaitceva (Кубанский научный медицинский вестник, 2016)
The aim of the work was to study the characteristics of anxiety and depressive disorders in medical students. There have been continuous cross-sectional complex clinical and epidemiological, clinical and psychopathological examination of 976 students of the first and fifth courses of all faculties. The main methods used in clinical and epidemiological, clinical, psychopathological, statistical methods. As a screening tool used by Hospital Anxiety and Depression Scale HADS. The prevalence of anxiety and depressive disorders of different nosology among medical students was 6.8% in the first year and 11.5% - in the fifth, with a prevalence of clinically significant anxiety in the first year and a significant prevalence of clinically significant depression in fifth, with a predominance of girls.